Heart rate and stroke rate misrepresent supramaximal sprint kayak training as quantified by power. Issue 5 (4th May 2021) - Hogan, Cruz; Binnie, Martyn J.; Doyle, Matthew; Lester, Leanne; Peeling, Peter
Abstract: This study examined the utility of novel measures of power output (PO) compared to traditional measures of heart rate (HR) and stroke rate (SR) for quantifying high-intensity sprint kayak training. Twelve well-trained, male and female sprint kayakers (21.3 ± 6.8 y) completed an on-water graded exercise test (GXT) and a 200-, 500- and 1000-m time-trial for the delineation of individualised training zones (T) for HR (5-zone model, T1-T5), SR and PO (8-zone model, T1-T8). Subsequently, athletes completed two repeat trials of a high-intensity interval (HIIT) and a sprint interval (SIT) training session, where intensity was prescribed using individualised PO-zones. Time-in-zone (minutes) using PO, SR and HR was then compared for both HIIT and SIT. Compared to PO, time-in-zone using HR was higher for T1 in HIIT and SIT ( P < 0.001, d ≥ 0.90) and lower for T5 in HIIT ( P < 0.001, d = 1.76). Average and peak HR were not different between HIIT (160 ± 9 and 173 ± 11 bpm, respectively) and SIT (157 ± 13 and 174 ± 10 bpm, respectively) ( P ≥ 0.274). In HIIT, time-in-zone using SR was higher for T4 ( P < 0.001, d = 0.85) and was lower for T5 ( P = 0.005, d = 0.43) and T6 ( P < 0.001, d = 0.94) compared to PO. In SIT, time-in-zone using SR was lower for T7 ( P = 0.001, d = 0.66) and was higher for T8 ( P = 0.004, d = 0.70), compared to PO. Heart rate measures were unable to differentiate training demands across different high-intensity sessions, and could therefore misrepresent the training load in such instances. Furthermore, SR may not provide a sensitive measure for detecting changes in intensity due to fatigue, whereas PO may be more suitable.